The Conversion of spaces and places of worship in Anatolia international conference 10-11 April 2021 - Azak, Umut 1973-; Dreßler, Markus; Girardelli, Paolo; Langer, Robert 1967-; Bermek, Doğan; Obaldia, Vanessa R. de (ADO Alevi Düşünce Ocağı ; ADİP Anadolu Din ve İnançları Platformu, 2021)
Osmanisches Reich -- Türkei -- Gotteshaus -- Kirche -- Moschee -- Umwidmung -- Profanbau -- Kongress -- Istanbul -- 2021